Clinicopathological characteristics of multiple intracranial Rosai-Dorfman disease with increased IgG4-positive plasma cells: a report of two cases - Zhou, Chunhui; Ren, Hongxiang; Hong, Liu; Zhang, Jianning; Wang, Hongxiang (Folia Neuropathologica, 2021)
Rosai-Dorfman disease (RDD) is an uncommon condition characterized by the proliferation of histiocytes and multiple intracranial involvements and it is extremely rare. Here, we present two cases of multiple intracranial RDD mimicking meningioma. These patients underwent surgery for tumour resection and pathological findings revealed an increased number of IgG4-positive plasma cells in RDD. The radiographic appearance and histology may contribute to a diagnostic dilemma, and immunohistochemical and serological examinations are a necessary complement for definitive diagnosis. Treatment protocols pertaining to such types of RDD cases are reviewed. Currently, surgical resection is the most effective therapy, and steroid therapy, radiotherapy, or chemotherapy may be provided as adjuvant treatments in some selected patients.